OC-020 INCISIONAL HERNIA REPAIR WITH MESH REIMAGINED: PILOT STUDY USING ABDOMINOPLASTY AS PERMANENT AUTOLOGOUS BIOLOGICAL REINFORCEMENT IN HERNIA REPAIR. (13th October 2022) - Tung, R; Fadaee, N; Rahban, R; Towfigh, S
Abstract: Aim: EHS consensus recommends mesh implantation for all incisional hernia (IH) repairs, regardless of size. We propose considering abdominoplasty in the algorithm for IH repairs wherein the plicated fascia functions as a permanent autologous biologic onlay repair over the primary repair of the IH. Materials & Methods: Four patients with midline IHs underwent abdominoplasty. Their IHs were first closed primarily with #2–0 permanent suture. Next, a two-layer anterior plication of the overlying fascia was performed with permanent suture. No mesh was implanted. Patients were followed up post operatively to monitor for hernia recurrence. Results: All patients were female with average age 51 years. All had at least one midline IH (1cm-1.7cm wide). Three (75%) had recurrent IHs. Three (75%) had diastasis recti. Patients were followed at 1 year, with no (0%) recurrence. Conclusion: Abdominoplasty may be a safe and effective alternative for IH repair compared to traditional mesh-based repair. In effect, the patient's own plicated fascia functions as a permanent autologous biologic onlay reinforcement to the IH repair. Meanwhile, the plication may reduce tension off the primary defect closure, thus reducing recurrence. Our pilot study in small IHs showed no hernia recurrence one-year postoperatively after abdominoplasty. Thus, abdominoplasty may serve as an alternative surgical option to a subset of patients with IH. We aim to judiciously expand indications for abdominoplasty for IH repair to address wider defects in select candidates. We hope our experience will supplement the current algorithm for IH repairs by providing a non-mesh alternative.